Alpha-1 Antitrypsin for COVID-19 Treatment: Dual Role in Antiviral Infection and Anti-Inflammation - Yang, Chengliang; Keshavjee, Shaf; Liu, Mingyao (Frontiers in Pharmacology, 2020)
Many drugs have been approved for clinical trials for the treatment of COVID-19 disease, focusing on either antiviral or anti-inflammatory approaches. Combining antiviral and anti-inflammatory drugs or therapies together may be more effective. Human alpha-1 antitrypsin (A1AT) is a blood circulating glycoprotein that is best known as a protease inhibitor. It has been used to treat emphysema patients with A1AT deficiency for decades. We and others have demonstrated its role in reducing acute lung injury by inhibiting inflammation, cell death, coagulation, and neutrophil elastase activation. Recently, A1AT has been found to inhibit severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection by inhibiting transmembrane serine protease 2 (TMPRSS2), a protease involved in the entry of SARS-CoV-2 into host cells. This dual role of both antiviral infection and anti-inflammation makes A1AT a unique and excellent candidate for COVID-19 treatment. Three clinical trials of A1AT for COVID-19 treatment have recently been approved in several countries. It is important to determine whether A1AT can prevent the progress from moderate to severe lung injury and eventually to be used to treat COVID-19 patients with acute respiratory distress syndrome.